Pengaruh Model Project Based Learning Berbantuan ArcGIS Terhadap Kemampuan Berpikir Spasial Siswa SMA - Rizqy, Iftinan Merthatul; Suharto, Yusuf; Risqiyati, Risqiyati (Cetta: Jurnal Ilmu Pendidikan, 2025)
Spatial thinking is defined as a person's ability to think about how to understand space by connecting certain interrelated objects so as to answer spatial problems from simple to complex. Based on facts in the field, students' spatial thinking skills are still relatively low at the high school level in Indonesia due to the minimal use of geography learning media, limited student activities, and textbook questions that require a high mastery of spatial concepts. In addition, based on a needs analysis, as many as 39.2% - 47.8% of students stated that the application of appropriate media greatly helped them in understanding the material. The use of the ArcGIS application and the Project Based Learning approach can provide students with direct experience in the learning process and students can understand the steps of managing geographic information system data to create base maps. The study was conducted to determine whether or not there is an effect of Project Based Learning with the help of the ArcGIS application on students' spatial thinking skills. This type of research is a quasi-experimental study with the experimental class and the control class as research subjects. Based on the results of the study, students' spatial thinking skills are significantly influenced by Project Based Learning (PBM) with the help of the ArcGIS application. This is indicated by the Asymp value. Sig (2-tailed) < 0.001 which is smaller than 0.05. In addition, the N-Gain Score results of the experimental class were higher than the control class, namely 53.5%. The practical benefit of this study is that it can be a reference for geography teachers in implementing technology-based learning based on Geographic Information Systems (GIS) by utilizing the ArcGIS application.